2018
DOI: 10.1016/j.athoracsur.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Elephant Trunk for Acute Type B Dissection Involving the Distal Arch in the Hybrid Repair Era

Abstract: Open repair of ATBAD with distal aortic arch involvement using the frozen elephant trunk procedure with LSCA-LCCA transposition obtained satisfactory outcomes. Avoidance of complications using hybrid repair, good postoperative recovery, and a low prevalence of late reintervention were achieved. The satisfactory results favored this technique for this lesion in this hybrid repair era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Okita et al [18] reported an hospital mortality rate of 2.4% with an incidence of spinal cord injury of 3.5% with the Frozenix device. Similar results were reported in other studies from Japan [19], China [20] and Canada [21]. In Bologna, between 2007 and 2021, 343 patients underwent aortic surgery with Frozen Elephant Trunk.…”
Section: Review Of the Literature And Bologna Experience In Different Aortic Pathologiessupporting
confidence: 88%
“…Okita et al [18] reported an hospital mortality rate of 2.4% with an incidence of spinal cord injury of 3.5% with the Frozenix device. Similar results were reported in other studies from Japan [19], China [20] and Canada [21]. In Bologna, between 2007 and 2021, 343 patients underwent aortic surgery with Frozen Elephant Trunk.…”
Section: Review Of the Literature And Bologna Experience In Different Aortic Pathologiessupporting
confidence: 88%
“…However, if the pathology involves the distal aortic arch, open surgery would be the first consideration in our center. LAA‐LCCA transposition or hemi‐arch replacement with stented elephant trunk implantation under hypothermic cardiopulmonary bypass with selective antegrade cerebral perfusion has been demonstrated to obtain satisfactory outcomes in our center 4,5 …”
Section: Discussionmentioning
confidence: 91%
“…Recently, frozen elephant trunk implantation has revolutionized the surgical strategy used for TAAD and TBAD repair. 13 , 14 For example, the distal anastomosis site is shallower with use of this technique; therefore, performing the anastomosis is easier and safer. We used a frozen elephant trunk in a patient with complicated TBAD.…”
Section: Discussionmentioning
confidence: 99%